Clinical assessment of endothelial function in convalescent COVID-19 patients: a meta-analysis with meta-regressions. (31st December 2022) - Ambrosino, Pasquale; Sanduzzi Zamparelli, Stefano; Mosella, Marco; Formisano, Roberto; Molino, Antonio; Spedicato, Giorgio Alfredo; Papa, Antimo; Motta, Andrea; Di Minno, Matteo Nicola Dario; Maniscalco, Mauro
Abstract: Background: Endothelial dysfunction has been proposed to play a key role in the pathogenesis of coronavirus disease 2019 (COVID-19) and its post-acute sequelae. Flow-mediated dilation (FMD) is recognized as an accurate clinical method to assess endothelial function. Thus, we performed a meta-analysis of the studies evaluating FMD in convalescent COVID-19 patients and controls with no history of COVID-19. Methods: A systematic literature search was conducted in the main scientific databases according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Using the random effects method, differences between cases and controls were expressed as mean difference (MD) with 95% confidence intervals (95% CI). The protocol was registered on PROSPERO with reference number CRD42021289684. Results: Twelve studies were included in the final analysis. A total of 644 convalescent COVID-19 patients showed significantly lower FMD values as compared to 662 controls (MD: −2.31%; 95% CI: −3.19, −1.44; p < 0.0001). Similar results were obtained in the sensitivity analysis of the studies that involved participants in either group with no cardiovascular risk factors or history of coronary artery disease (MD: −1.73%; 95% CI: −3.04, −0.41; p = 0.010). Interestingly, when considering studies separately based on enrolment within or after 3 months of symptom onset, results were further confirmed in both short- (MD: −2.20%; 95% CI: −3.35, −1.05; p < 0.0001) and long-term follow-up (MD: −2.53%; 95% CI: −4.19, −0.86; p = 0.003). Meta-regression models showed that an increasing prevalence of post-acute sequelae of COVID-19 was linked to a higher difference in FMD between cases and controls (Z-score: −2.09; p = 0.037). Conclusions: Impaired endothelial function can be documented in convalescent COVID-19 patients, especially when residual clinical manifestations persist. Targeting endothelial dysfunction through pharmacological and rehabilitation strategies may represent an attractive therapeutic option. Key messages: The mechanisms underlying the post-acute sequelae of coronavirus disease 2019 (COVID-19) have not been fully elucidated. Impaired endothelial function can be documented in convalescent COVID-19 patients for up to 1 year after infection, especially when residual clinical manifestations persist. Targeting endothelial dysfunction may represent an attractive therapeutic option in the post-acute phase of COVID-19.